On an {\it a priori} $L^∞$ estimate for a class of Monge-Ampère type equations on compact almost Hermitian manifolds - Masaya Kawamura (Cubo, 2022)
We investigate Monge-Ampère type equations on almost Hermitian manifolds and show an a priori $L^∞$ estimate for a smooth solution of these equations.